PEMBERDAYAAN EKONOMI JEMAAT DI TENGAH PANDEMI COVID 19 - Matuntu Elfie; Yusup Rogo Yuono; Agung Dian Rengganis; Yeriyusu Laoli (SAGACITY : Journal of Theology and Christian Education, 2022)
The church is an institution with a position as an organization as well as anorganism. The church as an organism needs to think about the survival of itsindividuals. The church has the responsibility to realize the Kingdom of God onearth, is present to give attention and answers. This study aims to review thechurch's pastoral efforts in the midst of the COVID-19 pandemic in empoweringcongregations, especially in the economic field. Christianity believes in the conceptof an integral mission of complete salvation. The church exists to contribute to thewelfare of the people. Prosperous in all aspects, both spiritual, mental, social andphysical aspects. The figure of the leader/shepherd becomes the central figure thatdetermines the success of the empowerment project. The sharpness of the leader inseeing the natural potential, the potential of the people and the interests of thepeople are factors that influence the success of the economic empowerment processin the local church community